2014
DOI: 10.1177/1461444814549930
|View full text |Cite
|
Sign up to set email alerts
|

“He has a way gayer Facebook than I do”: Investigating sexual identity disclosure and context collapse on a social networking site

Abstract: This study extends previous research into social networking sites (SNSs) as environments that often reduce spatial, temporal, and social boundaries, which can result in collapsed contexts for social situations. Context collapse was investigated through interviews and Facebook walkthroughs with 27 LGBTQ young people in the United Kingdom. Since diverse sexualities are often stigmatized, participants' sexual identity disclosure decisions were shaped by both the social conditions of their online networks and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
193
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 165 publications
(225 citation statements)
references
References 36 publications
15
193
1
3
Order By: Relevance
“…This interconnection leads to a reduction in social boundaries, often referred to as context collapse, which in turn results in information sharing across diverse network subgroups (boyd, 2010; Duguay, 2016; Fox & Ralston, 2016; Hogan, 2010; Vitak & Ellison, 2012). To manage outness in this context, LGBTQ youth reported using identity management strategies such as privacy controls, selectively adding friends, creating multiple accounts, restricting self-expression, deleting or untagging posts, selectively displaying information, and restricting LGBTQ-related content to more anonymous online forums (Cooper & Dzara, 2010; Duguay, 2016). Youth also reported frustration with the difficulty and effort these strategies required, as well as some lack of control over information sharing and pressure to connect with professional and family network members on Facebook (Cooper & Dzara, 2010; Duguay, 2016; Fox & Moreland, 2015; Roundtree, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This interconnection leads to a reduction in social boundaries, often referred to as context collapse, which in turn results in information sharing across diverse network subgroups (boyd, 2010; Duguay, 2016; Fox & Ralston, 2016; Hogan, 2010; Vitak & Ellison, 2012). To manage outness in this context, LGBTQ youth reported using identity management strategies such as privacy controls, selectively adding friends, creating multiple accounts, restricting self-expression, deleting or untagging posts, selectively displaying information, and restricting LGBTQ-related content to more anonymous online forums (Cooper & Dzara, 2010; Duguay, 2016). Youth also reported frustration with the difficulty and effort these strategies required, as well as some lack of control over information sharing and pressure to connect with professional and family network members on Facebook (Cooper & Dzara, 2010; Duguay, 2016; Fox & Moreland, 2015; Roundtree, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…To manage outness in this context, LGBTQ youth reported using identity management strategies such as privacy controls, selectively adding friends, creating multiple accounts, restricting self-expression, deleting or untagging posts, selectively displaying information, and restricting LGBTQ-related content to more anonymous online forums (Cooper & Dzara, 2010; Duguay, 2016). Youth also reported frustration with the difficulty and effort these strategies required, as well as some lack of control over information sharing and pressure to connect with professional and family network members on Facebook (Cooper & Dzara, 2010; Duguay, 2016; Fox & Moreland, 2015; Roundtree, 2016). Alternatively, some viewed context collapse positively because it allowed them to easily and efficiently come out to their entire network (Duguay, 2016; Hillier et al, 2012; Taylor et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While Facebook is the most dominant platform in many countries (Duggan, 2015;Sensis, 2016), several studies have already explored its implications for identity presentation (Lingel & Golub, 2015;Rains & Brunner, 2015;Zhao et al, 2013). Findings from my previous research (Duguay, 2016a) align with Bernie Hogan's (2010) analysis that Facebook's features for connecting multiple audiences can lead users to self-censor aspects of their identity. Conducting a pilot study with Twitter, I tracked activity relating to an LGBTQ festival but found that users tended to retweet celebrities and politicians without sharing much about their own sexual identity (Duguay, 2016b).…”
Section: Platformssupporting
confidence: 51%
“…LGBTQ university students negotiated collapsed contexts on Facebook, identifying how some students intentionally collapsed audiences together for coming out posts while others rebuilt contexts through coded messages and applying privacy settings (Duguay, 2016a telephone-based precursor to the internet) constructed elaborate pseudonyms, which concealed their legal names but also divulged information about their physique and sexual preferences to simultaneously create a "sense of secrecy, privacy and dangerous pleasure" (p. 204). In contrast, a lesbian Minitel community required users to purchase an annual subscription, which was viewed as providing the security necessary for users to be 'out' to one another, posting under their first names (Chaplin, 2014).…”
Section: Managingmentioning
confidence: 99%